2021
DOI: 10.4103/jfmpc.jfmpc_1963_20
|View full text |Cite
|
Sign up to set email alerts
|

Gliomas - An experience based on molecular markers

Abstract: Background: Gliomas account for 45% of all intracranial tumors. Newer technologies have allowed deeper genetic and epigenetic analysis leading to the discovery of IDH (Isocitrate dehydrogenase) mutations and their association with ATRX (alpha-thalassemia/mental retardation syndrome X-linked) and p53, for better diagnosis and prognosis. In this study, we analysed their expression and correlated with various clinicopathological parameters. A follow up to prognosticate gliomas based on the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In conclusion, as Sarma et al reported, 20,33 we think combined IHC markers for IDH1R132H, P53, and ATRX significantly improve the molecular classification of adult diffuse gliomas in daily practice, especially in low resources area where molecular tests are not widely available. The IHC results can be used as a guide for the selection of limited cases for co-deletion testing.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In conclusion, as Sarma et al reported, 20,33 we think combined IHC markers for IDH1R132H, P53, and ATRX significantly improve the molecular classification of adult diffuse gliomas in daily practice, especially in low resources area where molecular tests are not widely available. The IHC results can be used as a guide for the selection of limited cases for co-deletion testing.…”
Section: Discussionmentioning
confidence: 63%
“…Positive mutation has a considerable favorable impact on diffuse glioma behavior, irrespective of any other marker 15 . IDH mutation is frequent in histological grade 2and 3 astrocytomas 18,19 and is seen in about 70% to 90% of them as well as about 80% of oligodendrogliomas 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IDH mutant Astrocytoma is an infiltrative glioma of neoplastic astrocytes that diffusely invade glial tissue. Its diagnosis is supported by mutations of p53 and ATRX genes [3,4]. IDH mutation analysis is now a prerequisite for diagnosing an Astrocytoma, and research shows that these mutations appear to confer a significant survival advantage over their wild-type counterparts [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%